2020
DOI: 10.1200/jco.2020.38.15_suppl.e15108
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on survival rates in patients receiving immune checkpoint inhibitors.

Abstract: e15108 Background: Obesity is associated with 13 different cancer types, accounting for 40% of all cancers1. A few studies have linked a higher Body Mass Index (BMI) with longer Progression Free Survival (PFS) and Overall Survival (OS) from immune checkpoint inhibitors (CPI)s in patients with advanced melanoma, non-small cell lung cancer, and renal cell carcinoma2,3,4. Our study evaluates CPI efficacy in patients with multiple tumor types in relation to Body Mass Index (BMI). Methods: We retrospectively colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This study showed improved clinical outcomes in patients with high BMI who were treated with ICPIs compared to patients with healthy BMI with no statistically significant difference in the frequency of immune-related adverse events [95]. This observation is supported by Maslov et al, who demonstrated that high BMI in patients with metastatic cancer, across 20 different tumour types, is associated with a 48% lower risk of disease progression or death compared to patients with healthy BMI [96]. In addition, in a cohort of 250 patients diagnosed with several types of cancers who were treated with ICPIs, individuals with a BMI ≥ 30 had significantly better progression-free survival and OS compared to patients without obesity [31].…”
Section: Adiposity and Response To Cancer Immunotherapy In Breast Cancersupporting
confidence: 69%
“…This study showed improved clinical outcomes in patients with high BMI who were treated with ICPIs compared to patients with healthy BMI with no statistically significant difference in the frequency of immune-related adverse events [95]. This observation is supported by Maslov et al, who demonstrated that high BMI in patients with metastatic cancer, across 20 different tumour types, is associated with a 48% lower risk of disease progression or death compared to patients with healthy BMI [96]. In addition, in a cohort of 250 patients diagnosed with several types of cancers who were treated with ICPIs, individuals with a BMI ≥ 30 had significantly better progression-free survival and OS compared to patients without obesity [31].…”
Section: Adiposity and Response To Cancer Immunotherapy In Breast Cancersupporting
confidence: 69%
“…This observation is supported by Maslov et. al., who demonstrated that high BMI in patients with metastatic cancer, across 20 different tumour types, is associated with a 48% lower risk of disease progression or death compared to patients with healthy BMI [76]. In addition, in a cohort of 250 patients diagnosed with different types of cancers who were treated with ICPI, individuals with a BMI ≥30 had significantly better progression-free survival and OS compared to patients without obesity [50].…”
Section: Adiposity and Response To Cancer Immunotherapy In Breast Cancermentioning
confidence: 98%
“…This observation is supported by Maslov et. al., who demonstrated that high BMI in patients with metastatic cancer, across 20 different tumour types, is associated with a 48% lower risk of disease progression or death compared to patients with healthy BMI (69). In addition, in a cohort of 250 patients diagnosed with several types of cancers who were treated with ICPI, individuals with a BMI ≥30 had significantly better progression-free survival and OS compared to patients without obesity (70).…”
Section: Adiposity and Response To Cancer Immunotherapy In Breast Cancermentioning
confidence: 98%